The Effect of Overall Quality and Self-Efficacy on Learners' Flow and Satisfaction in Post-Pandemic Distance Learning - Diana Setiawati; Fanny Martdianty (Green Publisher Indonesia, 2024)
The objective of this study is to determine the effect of overall quality and self-efficacy on the flow and satisfaction of distance learning learners in the post-pandemic period in public sector organizations. Research data were collected through an online survey of distance learning participants in public sector organizations. A total of 701 data were analyzed. The data analysis method used was CB-SEM using Lisrel 8.80. This study found that system quality, information quality, and flow significantly and positively affected the satisfaction of distance learning participants. Self-efficacy, information quality, and service quality also have a positive and significant effect on the satisfaction of distance learning participants through the mediation of flow. Many previous studies have explored the effect of overall quality on online learning satisfaction in school or universities. However, this study is different in that it focuses on the context of public sector organizations by adding self-efficacy variables as internal factors of learners and including flow variables as mediators, considering that learners and instructors are not in the same location during distance learning. According to the findings from the conducted research, this study recommends that education and training organizers in the public sector can pay attention to factors that affect learner satisfaction in distance learning which include self-efficacy, overall learning quality, and flow in learning.